PERAN SERTIFIKASI INDUSTRI MELALUI PROGRAM BOOTCAMP DALAM MEMPERSIAPKAN MAHASISWA MEMASUKI DUNIA KERJA - Harry Z. Soeratin; Amanda Sabrina Nadyaputri; Dewi Krisna Murti; Davin Raditya; Widya Wiratami; Najma Muthia Kanza (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Student readiness to face the world of work is an important issue amidst the tight competition and rapid changes in industry needs. Students are required not only to master theory, but also to have practical skills and relevant competency recognition. This study aims to examine the role of industrial certification obtained through a bootcamp program in preparing students to enter the world of work. The method used is a literature review, by examining ten scientific journals published in the last five years that are relevant to the topics of certification, bootcamp, and student work readiness. The results of the study show that industrial certification through a bootcamp program makes a significant contribution to improving student work readiness, both in terms of technical skills and soft skills. Certification is not only proof of formal competence recognized by the industry, but also increases the confidence and competitiveness of graduates.